The Influence of Occupational Safety and Health, Job Satisfaction, and Organizational Climate on Organizational Commitment and Their Impact on Performance - Rembulan, Glisina Dwinoor; Alfonsus Ligouri Nikarsten Cindera, (JENIUS (Jurnal Ilmiah Manajemen Sumber Daya Manusia), 2026)
This study examines the effects of occupational safety and health (OSH), organizational climate, and job satisfaction on organizational commitment and their subsequent impacts on employee performance at PT BMKU, a steel and iron distribution and manufacturing company operating in West Jakarta. The research employed a quantitative approach using a survey questionnaire with a 5-point Likert scale, followed by instrument validity and reliability assessments. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS, supported by preliminary validity testing using SPSS. The measurement model evaluation indicates that all constructs meet adequacy criteria, including average variance extracted (AVE) values exceeding 0.50. The structural model demonstrates good fit (SRMR = 0.049) and strong predictive relevance (Q² = 0.915). Hypothesis testing reveals that OSH, organizational climate, and job satisfaction have positive and significant effects on both organizational commitment and employee performance; organizational commitment also positively and significantly affects performance (p < 0.001). Collectively, the model explains 88% of the variance in employee performance (Adjusted R² = 0.880) and 78.5% of the variance in organizational commitment (Adjusted R² = 0.782). However, mediation testing indicates that organizational commitment does not significantly mediate the relationships between OSH, organizational climate, and job satisfaction and employee performance (p for indirect effects = 0.216; 0.155; 0.325). These findings suggest that strengthening OSH practices, fostering a supportive organizational climate, and improving job satisfaction tend to exert direct effects on performance, while simultaneously enhancing organizational commitment as an important human resource management outcome at PT BMKU.